2020
DOI: 10.1109/access.2020.3020020
|View full text |Cite
|
Sign up to set email alerts
|

Proposal and Analysis of a Novel Class of PUFs Based on Galois Ring Oscillators

Abstract: In this paper, the possibility of using Galois ring oscillators to construct physically unclonable functions (PUFs) has been studied. The idea is to use novel PUF architectures, similar as the ring oscillator PUFs that, instead of comparing frequencies, compare the statistical bias of pairs of oscillators implemented in different locations. To study the viability of these systems, three different Galois oscillators have been implemented in several locations in several FPGAs and we have studied the main propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In [18], it was shown experimentally that the bias of GAROs changed with their location in a reproducible way and, therefore, they could be used to construct a PUF. As a proof of concept, a 7-LUT PUF that compared the bias of neighboring GAROs was implemented achieving an average Intra-chip Hamming Distance (Intra-HD) of ~1 % and an average Inter-chip Hamming Distance (Inter-HD) of ~39 %.…”
Section: A Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In [18], it was shown experimentally that the bias of GAROs changed with their location in a reproducible way and, therefore, they could be used to construct a PUF. As a proof of concept, a 7-LUT PUF that compared the bias of neighboring GAROs was implemented achieving an average Intra-chip Hamming Distance (Intra-HD) of ~1 % and an average Inter-chip Hamming Distance (Inter-HD) of ~39 %.…”
Section: A Backgroundmentioning
confidence: 99%
“…Furthermore, some works have proven that the behavior of these systems can greatly depend on the location within the FPGA so that, in certain locations, these systems can present poor randomness results [17]. Based on this fact, [18] studied the possibility of using the variations with the location presented by the GAROs to construct a PUF. That work showed that the bias of these systems varied with the location in a similar manner as the frequencies of a ring oscillator and, therefore, it was possible to use GAROs to construct a PUF in an analogous manner as an RO-PUF but comparing biases instead of frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the CRP space and hence improve security we propose a modified RO derived form a Galois linear feedback shift register (LFSR). A complementary design can be found in Garcia-Bosque et al (2020). In the design of Garcia-Bosque et al ( 2020) the inverters and XOR gates are connected in series and are always in the path of the system.…”
Section: Enhanced Configurable Ring Oscillator Physically Unclonable Functionsmentioning
confidence: 99%
“…It uses complex XOR feedback that is analogous to the Galois, thus creating Galois ring oscillators (GAROs). It is well known that the oscillators implemented in different locations in an integrated circuit present statistically significant differences [ 15 ]. Consequently, a GARO-based PUF compares the value of the bias of the GARO’s state instead of the frequencies of ring oscillators.…”
Section: Relevant Workmentioning
confidence: 99%